1988
DOI: 10.1073/pnas.85.16.5992
|View full text |Cite
|
Sign up to set email alerts
|

Biparental defensive endowment of eggs with acquired plant alkaloid in the moth Utetheisa ornatrix.

Abstract: The eggs of Utetheisa ornatrix contain pyrrolizidine alkaloids. These compounds are contributed by both parents, who sequester them as larvae from their food plants.Females receive alkaloid from the males at mating, apparently by seminal infusion, and transmit this alkaloid together with alkaloid of their own to the eggs. Field and laboratory tests showed that the alkaloids protect eggs from predators. The alkaloidal contribution of the male, although smaller than that of the female, itself provides significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
133
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(140 citation statements)
references
References 17 publications
1
133
1
5
Order By: Relevance
“…C. cubana is not the only Utetheisa egg predator deterred by the alkaloids. Both a coccinellid beetle and an ant have been shown to reject alkaloid-laden Utetheisa eggs (24,25). In addition, the alkaloids protect Utetheisa adults and larvae against spiders (18,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…C. cubana is not the only Utetheisa egg predator deterred by the alkaloids. Both a coccinellid beetle and an ant have been shown to reject alkaloid-laden Utetheisa eggs (24,25). In addition, the alkaloids protect Utetheisa adults and larvae against spiders (18,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Adults from the caterpillars that fed on the green seeds were preyed less frequently by the spider Nephila clavipes, 1767 (Araneae: Nephilidae), when fed on the leaves of C. pallida (Ferro et al, 2006). Eggs of this insect have been rejected by Coccinellidae beetles (Dussourd et al, 1988), larvae of Ceraeochrysa cubana, 1861 (Neuroptera: Chrysopidae) (Eisner et al, 2000) and the ant Leptothorax longispinosus, 1863 (Hymenoptera: Formicidae) (Hare & Eisner, 1993). Coleomegilla maculata De Geer, 1775 and Cycloneda sanguinea, 1763 (Coleoptera: Coccinellidae), Diabrotica speciosa, 1824 and Cerotoma arcuatus , 1791 (Coleoptera: Chrysomelidae) and the unidentified larvae of Coccinellidae (Tavares et al, 2011b), also soil organisms have been observed in the cultures of C. juncea in Sete Lagoas, Minas Gerais State, Brazil (Tavares et al, 2011c), showing the importance of this culture as a refuge for harmful-insects and natural enemies.…”
Section: Discussionmentioning
confidence: 99%
“…Host plant and pheromone chemical similarity has been explained in the context of the exploitation of a preexisting female sensory system that is geared to find and identify host plants Conner et al 1981;Boppre and Schneider 1985;Meinwald 1987, 1995;Dussourd et al 1988Dussourd et al , 1991Baker 1989;Krasnoff and Dussourd 1989;Landolt and Phillips 1997). Here we invoke sexual selection as a new evolutionary route to the evolution of specialization in larval feeding.…”
mentioning
confidence: 99%
“…In the case of Lepidoptera, males produce courtship pheromones that are often structurally similar to compounds found in certain plants (Baker 1989). The arctiid moth Utetheisa ornatrix is particularly well known in this regard (Conner et al 1981;Meinwald 1987, 1995;Dussourd et al 1988Dussourd et al , 1991, but other species, as either larvae or adults, also acquire host plant chemicals for the production of pheromones. For example, some species of arctiid moths are known to sequester chemicals during the larval stage for later use as pheromones or as precursors of pheromones (Baker 1989;Landolt and Phillips 1997), and adult males of danaiine and ithomiine butterflies actively collect chemicals (usually alkaloids in plant material such as rotting fruits or broken twigs) to use as pheromones Pliske 1975).…”
mentioning
confidence: 99%